Impaired Bone Microarchitecture at Distal Radial and Tibial Reference Locations Is Not Related to Injury Site in Athletes With Bone Stress Injury. Issue 12 (October 2022) - Stürznickel, Julian; Hinz, Nico; Delsmann, Maximilian M.; Hoenig, Tim; Rolvien, Tim
Background: Bone stress injuries (BSIs) are common sports injuries that occur because of an imbalance between microdamage accumulation and removal through bone remodeling. The underlying bone phenotype has been assumed to be a contributing factor. However, the bone microarchitecture of athletes with BSI is not well characterized, and no study has investigated whether impaired bone microarchitecture is associated with bone composition or anatomic site of injury. Purpose/Hypothesis: This cross-sectional study characterizes the bone microarchitecture at distal radial and tibial reference locations in athletes with BSI. Based on previous dual-energy X-ray absorptiometry (DXA) findings, the aim was to compare anatomic injury sites, hypothesizing that athletes with BSIs in bones with greater trabecular composition show impaired bone microarchitecture parameters compared with those with BSIs in bones with greater cortical composition. Study Design: Cohort study; Level of evidence, 3. Methods: Athletes who had presented to our outpatient clinic because of a high-grade BSI (ie, stress fracture) were retrospectively included. Blood and urine samples were collected. Areal bone mineral density (aBMD) was assessed by DXA at the lumbar spine and both hips. Bone microarchitecture was analyzed by high-resolution peripheral quantitative computed tomography (HR-pQCT) at the distal radius and tibia. HR-pQCT parameters were expressed in relation to available sex-, age-, and device-adjusted reference values and compared with a cohort of 53 age- and sex-matched controls. Results: In total, 53 athletes had a BSI of the foot (n = 20), tibia/fibula (n = 18), pelvis (n = 9), femur (n = 5), or sternum (n = 1). Based on DXA measurements, a Z-score of −1.0 or lower was found in 32 of 53 (60.4%) of the athletes, of whom 16 of 53 (30.2%) had a Z score −2.0 or lower. While an impairment of cortical area ( P = .034 and P = .001) and thickness ( P = .029 and P < .001) was detected at the distal radius and tibia in the BSI cohort compared with controls, no differences in BMD or bone microarchitecture were observed between anatomic injury sites. Furthermore, no difference was revealed when BSIs were grouped into cortical- and trabecular-rich sites. Conclusion: Reduced aBMD and impaired cortical bone microarchitecture were present in a considerable number of athletes with BSI. Neither aBMD nor bone microarchitecture was related to the injury site, highlighting the multifactorial etiology of BSI.